CRUISE CONTROL USING PREVIEW INFORMATION ABOUT THE ROAD AHEAD - Bergquist, Stefan; Carlsson, Fredrik (My University, 2012)
Advanced driver assistance systems in cars and trucks are getting ever more sophisticated with an emphasis on improving fuel efficiency, safety, and driver convenience. In a few years advanced navigation systems that can provide detailed real-time information about the road ahead are expected to become available. For this reason, it is important to investigate how assistance systems can be improved when this type of information becomes available. In this thesis, the assignment is to improve an existing cruise control algorithm using foundation brakes by integrating information about the road ahead. The goal is that the behavior should resemble that of an experienced truck driver. By doing this, the algorithm assimilates potential energy available in downhill slopes. At the same time, speed conditions must be fulfilled and the brakes should be used in an effective way. An algorithm has been developed that achieves the desired behavior. Before entering a descent, the speed is allowed to drop down to a defined minimum speed. When in the slope, the auxiliary brakes are used continuously while the foundation brakes are used for short periods of time when the speed reaches a defined maximum value. The brakes are controlled so that the vehicle leaves the slope at the maximum allowed speed. In order to avoid brake disc wear and, in worst case, a sudden reduction of the brake capacity, the brake disc temperature is monitored. If necessary, the speed is reduced to reduce the utilization rate of the foundation brakes. The results show that the behavior of an experienced driver can be approximated when introducing preview information in to the cruise controller algorithm. It has further been shown that the algorithm has the potential to reduce the foundation brake use with up to 10% in specific scenarios, compared to an existing cruise controller. The same comparison shows that the developed algorithm assimilates more available energy due to the speed reduction before a slope starts. This is achieved with only small effects on the average speed.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport